Intraarticular treatment with integrin α10β1-selected mesenchymal stem cells affects microRNA expression in experimental post-traumatic osteoarthritis in horses - Andersen, Camilla; Walters, Marie; Bundgaard, Louise; Berg, Lise Charlotte; Vonk, Lucienne Angela; Lundgren-Åkerlund, Evy; Henriksen, Betina Lyngfeldt; Lindegaard, Casper; Skovgaard, Kerstin; Jacobsen, Stine (Frontiers in Veterinary Science, 2024)
Osteoarthritis (OA) remains a major cause of lameness in horses, which leads to lost days of training and early retirement. Still, the underlying pathological processes are poorly understood. MicroRNAs (miRNAs) are small non-coding RNAs that serve as regulators of many biological processes including OA. Analysis of miRNA expression in diseased joint tissues such as cartilage and synovial membrane may help to elucidate OA pathology. Since integrin a10b1-selected mesenchymal stem cell (integrin a10-MSC) have shown mitigating effect on equine OA we here investigated the effect of integrin a10-MSCs on miRNA expression. Cartilage and synovial membrane was harvested from the middle carpal joint of horses with experimentally induced, untreated OA, horses with experimentally induced OA treated with allogeneic adipose-derived MSCs selected for the marker integrin a10-MSCs, and from healthy control joints. miRNA expression in cartilage and synovial membrane was established by quantifying 70 pre-determined miRNAs by qPCR. Differential expression of the miRNAs was evaluated by comparing untreated OA and control, untreated OA and MSC-treated OA, and joints with high and low pathology score. A total of 60 miRNAs were successfully quantified in the cartilage samples and 55 miRNAs were quantified in the synovial membrane samples. In cartilage, miR-146a, miR-150 and miR-409 had significantly higher expression in untreated OA joints than in control joints. Expression of miR-125a-3p, miR-150, miR-200c and miR-499-5p was significantly reduced in cartilage from MSC-treated OA joints compared to the untreated OA joints. Expression of miR-139-5p, miR-150, miR-182-5p, miR-200a, miR-378, miR-409-3p and miR-7177b in articular cartilage reflected pathology score. Several of these miRNAs are known from research in human patients with OA and from murine OA models. Our study shows that these miRNAs are also differentially expressed in experimental equine OA, and that expression depends on OA severity. Moreover, MSC treatment, which resulted in less severe OA, also affected miRNA expression in cartilage.